Survival and personal identity in orphism - Megino Rodríguez, Carlos (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
The aim of the article is to clarify the conditions which are fulfilled by the soul in orphism in order to base on it the possibility of self-survival. To this end, we study what the soul consists of in orphism, analyzing all orphic testimonies that allow us to draw conclusions in connection with the role of the soul in the orphic conception of personal identity. We also take into account the role played by other factors in orphism, like the body and memory, as possible criteria for personal identity. Finally, we conclude that the soul in orphism is the bearer of the personal identity, because it is a substantive, individual and independent entity, of a unique and permanent nature, immortal and the subject of a unique and untransferable vital history.
Keywords: Survival; personal identity; orphism; immortality; soul.